Extracorporeal membrane oxygenation for respiratory failure in phases of COVID‐19 variants. Issue 10 (30th April 2022) - Shih, Emily; DiMaio, J. Michael; Squiers, John J.; Rao, Arundhati; Rahimighazikalayeh, Gelareh; Meidan, Talia C.; Monday, Kara A.; Blough, Britton; Meyer, Dan; Schwartz, Gary S.; George, Timothy J.
Abstract: Background: Adaptive mutations of the severe acute respiratory syndrome‐related coronavirus (SARS‐CoV‐2) virus have emerged throughout the coronavirus disease 2019 (COVID‐19) pandemic. The characterization of outcomes in patients requiring extracorporeal membrane oxygenation (ECMO) for severe respiratory distress from COVID‐19 during the peak prevalence of different variants is not well known. Methods: There were 131 patients with laboratory‐confirmed SARS‐CoV‐2 infection supported by ECMO at two referral centers within a large healthcare system. Three predominant variant phase time windows (Pre‐Alpha, Alpha, and Delta) were determined by a change‐point analyzer based on random population sampling and viral genome sequencing. Patient demographics and outcomes were compared. Results: The average age of patients was 46.9 ± 10.5 years and 70.2% (92/131) were male. Patients cannulated for ECMO during the Delta variant wave were younger compared to earlier Pre‐Alpha (39.3 ± 7.8 vs. 48.0 ± 11.1 years) and Alpha phases (39.3 ± 7.8 vs. 47.2 ± 7.7 years) ( p < .01). The predominantly affected race in the Pre‐Alpha phase was Hispanic (52.2%; 47/90), while in Alpha (61.5%; 16/26) and Delta (40%; 6/15) variant waves, most patients were White ( p < .01). Most patients received a tracheostomy (82.4%; 108/131) with a trend toward early intervention in later phases compared to Pre‐Alpha ( p < .01). There was no significant difference between the duration of ECMO, mechanical support, intensive care unit (ICU) length of stay (LOS), or hospital LOS over the three variant phases. The in‐hospital mortality was overall 41.5% (54/131) and was also similar. Six‐month survival of patients who survived to discharge was 92.2% (71/77). Conclusions: There was no significant difference in survival or time on ECMO support in patients during the peak prevalence of the three variants.